Ten friendly fish - Tarbett, Debbie (London : Little Tiger Press, 2008)
Ten friendly fish on a swim one day. One sees a starfish and splashes off to play!
Keywords: Counting -- Pictorial works; Fishes -- Pictorial works; Maths (Elementary); Stories in rhyme